2020
DOI: 10.1186/s41077-020-00126-0
|View full text |Cite
|
Sign up to set email alerts
|

In situ simulation training in helicopter emergency medical services: feasible for on-call crews?

Abstract: Simulation-based training of emergency teams offers a safe learning environment in which training in the management of the critically ill patient can be planned and practiced without harming the patient. We developed a concept for in situ simulation that can be carried out during on-call time. The aim of this study is to investigate the feasibility of introducing in situ, simulation-based training for the on-call team on a busy helicopter emergency medical service (HEMS) base. We carried out a one-year prospec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 15 publications
3
19
0
Order By: Relevance
“…The participating crews at all bases reported high satisfaction scores in their evaluations of the simulation training (Table 1). This is in accordance with ndings in a previous pilot study [8].…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…The participating crews at all bases reported high satisfaction scores in their evaluations of the simulation training (Table 1). This is in accordance with ndings in a previous pilot study [8].…”
Section: Discussionsupporting
confidence: 94%
“…The facilitators were encouraged to have speci c learning aims for each scenario and to ensure that no participants were exposed to the same scenario more than once. A total time consumption of one hour was regarded as optimal, but this could vary [8]. Facilitators were invited to share scenarios between bases.…”
Section: Scenarios and Equipmentmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous pilot study, we showed that in situ simulation is a feasible training concept for simulation-based training at the workplace during on-call hours for HEMS crews. 8 In that study, a simulation program was introduced at a busy HEMS base in Norway. The simulation-based training was shown to take up little time for the crews, and the response from the participating crews was generally very positive.…”
mentioning
confidence: 99%
“…The simulation-based training was shown to take up little time for the crews, and the response from the participating crews was generally very positive. 8 To our knowledge, no other program for simulationbased training of on-call HEMS crews has been implemented on a Supported by a research grant from the Norwegian Air Ambulance Foundation, who provided compensation for the facilitators as well as provided manikins and training equipment for bases in need of that.…”
mentioning
confidence: 99%